ANALYSIS OF SHORT CIRCUITED ANNULAR RING PATCH ANTENNA OPERATED AT TM01 MODE - González P.,Vicente (Universidad de Tarapacá. Facultad de Ingeniería, 2005)
This paper presents a comprehensive study of the theory of the short circuited annular-ring patch based on the cavity model. An analytical expression for frequency, fields, radiation pattern, efficiency and input impedance based on this model is shown. Simulations and experimental results are given to show the resonant frequencies, illumination fields, radiation patterns and input impedances for the 0 and 1 modes. Furthermore, it provides a simple formulation to design this type of antennas.